A classroom game on a negative externality correcting tax: Revenue return, regressivity, and the double dividend. Issue 2 (3rd April 2017) - Duke, Joshua M.; Sassoon, David M.
ABSTRACT: The concept of negative externality is central to the teaching of environmental economics, but corrective taxes are almost always regressive. How exactly might governments return externality-correcting tax revenue to overcome regressivity and not alter marginal incentives? In addition, there is a desire to achieve a double dividend in the use of externality-correcting taxes, that is, to use the revenue to offset existing distortionary taxes, such as those on labor that produce a dead weight loss. In this article, the authors explain a classroom game that was developed for students to understand the theory of externalities, taxation dead weight loss, and regressivity. Then, the problem helps students explore the actual design of a policy that satisfies the double dividend hypothesis and corrects for regressivity.